The Indian Hair-Wringing Apsaras and her Discriminating Goose. (27th January 2022) - Cohen, Simona
Abstract : The present study investigates depictions of the Indian apsaras wringing water from her hair in monumental religious iconography. It demonstrates the migration of iconography and transformations of meaning from the northern sources to other areas of India and ultimately to parts of southeast Asia. I examine ancient literary and visual sources of the hair-wringing apsaras, mediator of the life-giving celestial waters, and the goose that drinks her hair-water in Buddhist, Hindu and Jain artistic contexts, demonstrating expressions of abstruse theological concepts. The salient virtue of the mythic hamsa (migrating goose) was its ability to separate milk from water (nira-ksira-viveka). This discrimination, already mentioned in Vedic and later sources, was appropriated as a metaphoric image in moral, didactic, theological and philosophical contexts. Connotations implicit in the myth of the potent water that passes through the apsaras's hair are compared to those of the rejuvenating waters that flowed through Siva's ascetic locks in the myth of Gangadhara.